Analisis Perbandingan Tingkat Kebisingan Kabin Pada Mitsubishi Destinator Varian Sunroof dan Non-Sunroof Menggunakan Sound Level Meter - Faiz Arkan Yulianto; Yusep Sukrawan; Ridwan Adam M Noor; Tatang Permana; Gilang Ciptadi Mahatkarsa (JURNAL ILMIAH TEKNIK INDUSTRI DAN INOVASI, 2026)
This study aims to analyze and compare the cabin noise levels of the Mitsubishi Destinator Ultimate variant (sunroof) and Exceed variant (non-sunroof) under various driving speed conditions. Measurements were conducted using a Sound Level Meter inside the cabin at idle, 10, 30, 50, 70, 90, and 100 km/h. Results indicate that the Ultimate (sunroof) variant consistently produces higher noise levels than the Exceed (non-sunroof) variant across all speed variations. The largest noise difference was recorded at 100 km/h at 6.50 dB, while the smallest occurred at idle at 0.05 dB. Noise levels in both variants increased significantly with increasing speed, with the sunroof variant reaching 70.00 dB and the non-sunroof variant reaching 63.50 dB at 100 km/h. This difference is attributed to gaps and seals in the sunroof panel, which allow greater noise penetration from the external environment.